Implementation of Strengthening Integrity Character Education in Pancasila and Citizenship Education Learning for STIE Indragiri Rengat Management Study Program Students - Airine Yulianda; Kurnia Dewi; Hasanah Yaspita; Dewi Hartika (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to analyze the implementation of strengthening integrity character education in learning Pancasila and civics education for Management Study Program students at STIE-I Rengat. Pancasila and Citizenship Education is one of the basic general subjects in tertiary institutions which is the leading sector in the implementation of strengthening student integrity character education. However, in reality the Pancasila and Citizenship courses have not been optimal in carrying out this role because the processes that occur are still oriented towards cognitive achievement. In fact, Pancasila and civics education courses have not been successful enough to carry out this role properly because the processes that occur in educational learning are only activated in achievement, affective/attitude management is ignored. To overcome this, it is necessary to examine modifications in educational learning, one of which is by integrating the concept of character into its development so that it is better able to develop and shape the character of students in tertiary institutions, especially students of Management Study Program, STIE-I Rengat.